Effects of black weevil control (Cosmopolites sordidus) in plantains. - Armendáriz, Ignacio (2016)
The aim of this study was to test the effect of mass capture of adults using pheromone traps and applying entomopathogenic fungi on Cosmopolites sordidus. The research was conducted in El Carmen, Manabí, Ecuador, from December 2013 to October 2014, in a plot of new Barraganete plantain plantation. The effect of plant remains removal from the plots was also assessed. The experimental design was randomized complete block with three repetitions. The infectivity of Beauveria bassiana on adults of black weevil and brown weevil (Metamasius hemipterus) was evaluated in the laboratory(92.80 and 100% in M. hemipterus versus 46.70 and 16.20% in C. sordidus). Adult catches were continuous throughout the experiment, with an average of 0.37 adults/trap/day. Agronomic data indicated a positive and significant (analysis of variance) difference of treatment versus control at the perimeter of the pseudostem (4.982 F *) and bunch weight between plots with pheromones and plots with clean fungi versus control (F = 3.994 **). When comparing treatments, bunch weight and finger length were significantly higher in the plots treated with pheromones compared to the ones treated with fungi (F = 4.508 **). Catches of adults with pheromones were not conditioned by the cleaning of plots, though this did affect the plant height (F = 4.245 *).